Thrombocytopenia in malaria and its diagnostic significance: A prospective study - Prudhivi Krishna; Manoj Kumar Chalamalasetty (Journal of Clinical and Scientific Research, 2023)
Background: Thrombocytopenia is a common finding in malaria. Although a reliable diagnostic marker, prognostic implications could vary in the types of malaria. Methods: This hospital-based prospective study was carried out at our tertiary care teaching hospital. We studied the occurrence of thrombocytopenia, the association of thrombocytopenia with disease severity and outcome. Results: During the study period, 100 patients with malaria P. vivax (n = 42) and P. falciparum (n = 24) were studied. Their mean age was 42.4 ± 12.1 years; there were 76 males. were detected. Fever was present in 42 patients with P. vivax, 24 with P. falciparum and 34 patients with clinically diagnosed malaria. Thrombocytopenia was present in 81/100 cases. Conclusions: Thrombocytopenia is helpful in predicting the outcome of complicated malaria but does not help in the early diagnosis.